IFN-γ-dependent regulation of intestinal epithelial homeostasis by NKT cells - Marta Lebrusant-Fernandez; Tom ap Rees; Rebeca Jimeno; Nikolaos Angelis; Joseph C. Ng; Franca Fraternali; Vivian S.W. Li; Patricia Barral (Cell Reports)
Summary: Intestinal homeostasis is maintained through the combined functions of epithelial and immune cells that collaborate to preserve the integrity of the intestinal barrier. However, the mechanisms by which immune cell populations regulate intestinal epithelial cell (IEC) homeostasis remain unclear. Here, we use a multi-omics approach to study the immune-epithelial crosstalk and identify CD1d-restricted natural killer T (NKT) cells as key regulators of IEC biology. We find that NKT cells are abundant in the proximal small intestine and show hallmarks of activation at steady state. Subsequently, NKT cells regulate the survival and the transcriptional and cellular composition landscapes of IECs in intestinal organoids, through interferon-γ (IFN-γ) and interleukin-4 secretion. In vivo, lack of NKT cells results in an increase in IEC turnover, while NKT cell activation leads to IFN-γ-dependent epithelial apoptosis. Our findings propose NKT cells as potent producers of cytokines that contribute to the regulation of IEC homeostasis.